Potential for Tourism and Recreation in the Todzhinsky Kozhuun (District), Republic of Tyva, RF - Denis Dirin; Elena Rasputina; Maria Kuklina; Natalia Krasnoshtanova; Andrey Trufanov; Eduard Batosirenov; Galina Lysanova (Sustainability, 2023)
The paper reveals opportunities and limitations of tourism development in one of the most inaccessible areas in the mountains of Southern Siberia: Todzhinsky kozhuun, Republic of Tyva, RF. Taking into account key indicators that reflect the natural, historical, cultural, and socio-economic characteristics of the territory, using GIS technologies, a comprehensive assessment and mapping of the tourism and recreational potential (TRP) of the territory was carried out. The method of multicomponent scoring was used in this work. Consequentially, the study area was divided by means of a regular hexagonal network into many operational territorial cells; for each of those, the sum of scores was calculated according to the conditions and objects that are localized within its boundaries. The set of operational territorial cells filled with visual information made it possible to create an assessment map of the tourism and recreational potential of the Todzhinsky kozhuun territory. This map highlights the areas of the five value ranks, from the highest to the lowest. The areas with the highest scores are obviously the most suitable for the development of tourism industry. In general, the basis of the region’s TRP is picturesque virgin natural landscapes with many large lakes, unique traditional ethnocultural landscapes of the mountain–taiga reindeer herders, biological resources for hunting and fishing, and healing mineral springs (arzhany). The key limiting factor in the development of tourism is the underdeveloped transportation system and the insufficiency of special tourism infrastructure facilities. Such an assessment made it possible to identify territories favorable for the creation of three specialized tourist clusters: ethnocultural tourism, “Reindeer herders of Todzhi”; water, ecological, and fishing tourism, “Todzha Lakes”; and mountain and sports tourism, “Big Sayan”.